Genetic progress of grain quality of flooded-irrigated rice cultivars in the state of Rio Grande do Sul, Brazil - Streck, Eduardo Anibele; Magalhães Júnior, Ariano Martins de; Aguiar, Gabriel Almeida; Facchinello, Paulo Henrique Karling; Perin, Lais; Fagundes, Paulo Ricardo Reis; Oliveira, Antônio Costa de (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to determine the genetic progress of grain quality attributes of flooded irrigated rice (Oryza sativa) cultivars in the state of Rio Grande do Sul, Brazil, between 1972 and 2016. The genetic estimates followed an approach based on the comparative analysis of 25 cultivars released by Embrapa’s breeding program over this period. The experiment was implemented in four producing regions of the state of Rio Grande do Sul: Sul, Campanha, Planície Costeira Interna, and Planície Costeira Externa. The following significant genetic gains were observed: 0.20% per year, for percentage of whole grains after processing; -1.38% per year, for percentage of chalky kernels and white-core grains; -0.77% per year, for total chalky area; -0.08% per year, for total whiteness; and -0.82% per year, for non-vitreous grain whiteness. Most cultivars released have high amylose content and a low gelatinization temperature. Therefore, the breeding program presented significant annual genetic progresses between 1972 and 2016 for the main attributes of grain quality, and made cultivars available according to the national demand for grain quality in the several segments of the rice production industry.